Penerapan Mekanisme Keadilan Restoratif (Restorative Justice) di Lembaga Kejaksaan Republik Indonesia dalam Upaya Pemulihan Hak Korban Tindak Pidana dalam Perspektif Viktimologi Postmodern - Khairuummah, Rosdayana (Universitas Sultan Ageng Tirtayasa, 2023)
In criminal law, it recognizes retributive justice and restorative justice which over time law enforcement in Indonesia experiences supremacy in the judicial process where law enforcement officials are expected to be able to realize the supremacy of law enforcement through restorative justice which in the process of settling cases is carried out outside the court by involving victims, perpetrators as well as other stakeholders who are interconnected with each other in determining the process of running a restorative justice mechanism by taking into account the main interest, namely the fulfillment of victims' rights. The mechanism for the supremacy of law enforcement through restorative justice has been carried out by the Prosecutor's Office of the Republic of Indonesia based on the Attorney General's Regulation (PERJA) Number 15 of 2020 concerning Termination of Prosecution based on Restorative Justice. The implementation of the supremacy of law enforcement carried out by the Prosecutor's Office through restorative justice is a representative form of postmodern victimology theory which focuses on protecting the law from crime victims with the aim of recovering parties in conflict which are carried out informally.